2021
DOI: 10.1017/s0007114521004992
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of ultra-processed foods and the eating location: can they be associated?

Abstract: Studies indicate that eating locations can influence food choices. However, the relationship with ultra-processed foods has been little explored. The objective was to assess the association between eating locations and ultra-processed foods consumption in the UK in 2014-2016. Data from 2,449 individuals aged 4 years or older from the NDNS were analysed cross-sectionally. Food consumption information was collected through 4day food diaries. Recorded foods were classified into NOVA system. The eating locations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Results from a study in Brazil have suggested the consumption frequency of UPF can be higher when eating OH than when eating AH (50) . A study of adolescents in the United Kingdom, based on data from the National Diet and Nutrition Survey Rolling Program, showed that eating AH ( β = −0·12, 95 % CI (−0·19, −0·05)) was inversely associated with UPF consumption, while fast food consumption ( β = 0·29, 95 % CI (0·12, 0·47)) was directly associated with increased UPF consumption (21) . While cross-sectional studies on the relationship between intake and body size are often hampered by the inaccuracies of food intake measurement methods, larger and better-controlled studies on the topic suggest that eating more UPF away from home is associated with increased BMI and unfavourable changes in body fatness.…”
Section: Discussionmentioning
confidence: 99%
“…Results from a study in Brazil have suggested the consumption frequency of UPF can be higher when eating OH than when eating AH (50) . A study of adolescents in the United Kingdom, based on data from the National Diet and Nutrition Survey Rolling Program, showed that eating AH ( β = −0·12, 95 % CI (−0·19, −0·05)) was inversely associated with UPF consumption, while fast food consumption ( β = 0·29, 95 % CI (0·12, 0·47)) was directly associated with increased UPF consumption (21) . While cross-sectional studies on the relationship between intake and body size are often hampered by the inaccuracies of food intake measurement methods, larger and better-controlled studies on the topic suggest that eating more UPF away from home is associated with increased BMI and unfavourable changes in body fatness.…”
Section: Discussionmentioning
confidence: 99%
“…In the adjusted models, adolescents (aged 10-17) had the highest UPF intake, with female adolescents consuming 192 g (95% CI: 135, 249) more than female older adults, and male adolescents consuming 327 g (95% CI: 277, 377) more than male older adults (aged [45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64]. Female and male older adults (aged 45-64) consumed 63 g more (95% CI: 34, 91) and 51 g more (95% CI: 9, 93) than elderly females and males (aged [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. The difference in UPF intake across ages was greater in males than females (57) .…”
Section: Associations By Countrymentioning
confidence: 99%
“…UK. In the UK, average UPF intake was 51•3% (SD: 13•1) in 2008-2009 (≥19 years) (62) , 53•1% across 2008-2012 (≥18 years) (64) , 56•8% (SE: 0•2) across 2008-2014 (≥1•5 years) (65) , 54•3% (SE: 0•4) across 2008-2016 (19-96 years) (66) , and 54•0% in 2014-2016 (≥4 years) (67) . From 2008 to 2016, UPF intakes have been relatively consistent, with no significant linear trends in UPF intake across sociodemographic strata (63) .…”
Section: Associations By Countrymentioning
confidence: 99%
“…Eating environments have become of particular interest due to the role of environment on health and health behavior ( 6–8 ). Research has shown eating environment can influence energy intake ( 7 ), types of foods eaten, and rate of eating ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Eating environments have become of particular interest due to the role of environment on health and health behavior ( 6–8 ). Research has shown eating environment can influence energy intake ( 7 ), types of foods eaten, and rate of eating ( 6 ). Categorizing eating environments has proven challenging thus far for multiple reasons, largely dependent on an individual’s daily routine spanning across multiple environments throughout the day ( 4 ).…”
Section: Introductionmentioning
confidence: 99%